2022
DOI: 10.3390/genes13020208
|View full text |Cite
|
Sign up to set email alerts
|

miRNA and lncRNA Expression Networks Modulate Cell Cycle and DNA Repair Inhibition in Senescent Prostate Cells

Abstract: Cellular senescence is a state of permanent growth arrest that arises once cells reach the limit of their proliferative capacity. It creates an inflammatory microenvironment favouring the initiation and progression of various age-related diseases, including prostate cancer. Non-coding RNAs (ncRNAs) have emerged as important regulators of cellular gene expression. Nonetheless, very little is known about the interplay of microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) and how deregulation of ncRNA networks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“…This same microRNA is predicted from the miRTarBase to target ZNF365. We can speculate that the observed reduction in ZNF365 expression following doxorubicin treatment in our study could result from the same miRNA (senescence-associated miRNA [ 30 ]) or, since both molecules physically interact, they could work through feedback loops.…”
Section: Discussionmentioning
confidence: 99%
“…This same microRNA is predicted from the miRTarBase to target ZNF365. We can speculate that the observed reduction in ZNF365 expression following doxorubicin treatment in our study could result from the same miRNA (senescence-associated miRNA [ 30 ]) or, since both molecules physically interact, they could work through feedback loops.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies indicate that lncRNAs play integral roles in the occurrence and development of diverse tumors 16 , 17 . Additionally, lncRNAs are involved in mechanisms linked with aging including proliferation, differentiation, and apoptosis 18 . Recent studies have revealed that lncRNAs are directly linked to senescence.…”
Section: Introductionmentioning
confidence: 99%
“…The lncRNAs regulate many key cellular activities, including cell proliferation, apoptosis, differentiation, and metabolism [ 12 ]. In addition, lncRNAs regulate physiological and pathological processes such as cell cycle and DNA damage repair, whose disruption can result in the progression of malignant tumors [ 13 , 14 ]. Furthermore, lncRNAs can control the pathogenesis of CRC from a variety of angles, primarily involving the tumor microenvironment (TME) that includes inflammation, immune evasion and exosome secretion, epithelial-mesenchymal transition (EMT), stemness maintenance, and angiogenesis of tumor, thus allowing them to control the occurrence, development, and treatment of CRC [ 15 ].…”
Section: Introductionmentioning
confidence: 99%